Building a System for Finding Objections to an Argument. - Walton, Douglas (Argumentation, 2012)
This paper addresses the role that argumentation schemes and argument visualization software tools can play in helping to find and counter objections to a given argument one is confronted with. Based on extensive analysis of features of the argumentation in these two examples, a practical four-step method of finding objections to an argument is set out. The study also applies the Carneades Argumentation System to the task of finding objections to an argument, and shows how this system has some capabilities that are especially useful.